2019
DOI: 10.2147/cia.s195109
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association between frailty and the cardio-ankle vascular index</p>

Abstract: Purpose Frailty and atherosclerotic diseases are prevalent among the older people and usually present the same pathogenesis and risk factors. Therefore, the aim of this study was to determine the association between frailty and atherosclerosis. Patients and methods The enrolled participants were 171 patients aged 60–96 years in Beijing Tongren Hospital. Data that were collected included sex, age, height, weight, calculated body mass index (BMI), past medical history, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
4
24
0
1
Order By: Relevance
“…A number of factors influence both a single CAVI value and evaluation of this parameter over time, including age, sex, body mass index, frailty, serum uric acid levels, lipid levels, smoking status, and vascular tone 36‐41 . The relative contribution of these factors to our study findings, and the extent to which they influenced the results of earlier studies, cannot be determined.…”
Section: Discussionmentioning
confidence: 73%
“…A number of factors influence both a single CAVI value and evaluation of this parameter over time, including age, sex, body mass index, frailty, serum uric acid levels, lipid levels, smoking status, and vascular tone 36‐41 . The relative contribution of these factors to our study findings, and the extent to which they influenced the results of earlier studies, cannot be determined.…”
Section: Discussionmentioning
confidence: 73%
“…Im et al 90) observed a positive association of muscle mass deficits with arterial stiffness in middle-aged men. Xue et al 91) showed that CAVI is associated with frailty in older patients. These findings suggest that skeletal muscle loss not only promotes vascular aging, but atherosclerosis may also promote sarcopenia.…”
Section: (B) Sarcopeniamentioning
confidence: 99%
“…The outcomes of the study strongly suggested that atherosclerosis was associated with significantly worse walking speed test results achieved by patients. This shows that these patients are more predisposed to poorer mobility, strength and balance, which are features directly associated with criteria for the diagnosis of the frailty syndrome [ 72 ]. Similar conclusions were drawn from the results of the ARIC Study, which assessed the relationship of multiple parameters assessing cardiovascular function with a predisposition to Frailty, including echocardiography, ABI, pulse-wave-velocity, spirometry, estimated glomerular filtration rate, hemoglobin concentration, body mass index and bioimpedance [ 73 ].…”
Section: The Significance Of Ankle-brachial Index (Abi) and Toe-brmentioning
confidence: 99%